CORNTRA: Corn (Zea mays) Ribosome-Inactivating Protein Spray Against Fall Armyworm (Spodoptera frugiperda) - Galgo, Matteo Gabriel S.; Gallemit, Rhoda P.; Lavador, Prezzi Lah Mikha Lorraine M.; Rodriguez, Ray A.; Leppla, Norman C.; Leop, Glory Jean B.; Banggud, Annaliza A.; Rollon, Erick Venn R. (International Journal of Research in Interdisciplinary Studies, 2026)
The need for natural biocontrol agents has intensified due to the rising environmental impacts of synthetic insecticides and the increasing resistance of key agricultural pests, including the Fall Armyworm (Spodoptera frugiperda). The aim of the current study was to determine the time and effectiveness profile of CORNTRA, a novel maize-derived β-32 Ribosome-Inactivating Protein (RIP) biopesticide. Through solvent extraction and ammonium sulfate precipitation, a concentrated RIP stock was formulated with 5% ethanol and tested against 2nd–4th instar larvae. Bioassays revealed that CORNTRA achieved a 100.00% mean corrected mortality, numerically exceeding the 83.33% mortality of the 0.5% chlorpyrifos benchmark. One-way ANOVA confirmed significant treatment effects (F (2, 6) = 31.00, p = 0.0007), while Tukey’s HSD indicated no significant difference in lethal efficacy between CORNTRA and the synthetic control (p = 0.4736), showing their near-equal performance. Crucially, CORNTRA also demonstrated a significantly faster onset of action (F (2,6) = 61.00, p = 0.0001) in comparison to the synthetic control, greatly outperforming it (p = 0.0064). Overall, CORNTRA showed a superior performance profile, combining rapid activity with high efficacy, highlighting its potential as a sustainable and effective biopesticide for the control of S. frugiperda.